Стан про- та антиоксидантної систем у тимусі тварин з експериментальним алергічним альвеолітом - Матолінець, Т.М.; Матолінець, О.М. (Медична гідрологія та реабілітація, 2012)
В работе изучалось состояние про- и антиоксидантной систем в тимусе морских свинок на 74-е, 84-е, и 94-е сутки эксперимента в динамике экспериментального аллергического альвеолита. После проведения эксперимента было установлено постепенное понижение активности супероксиддисмутазы и каталазы с одновременным повышением уровня показателей прооксидантной системы в тимусе животных с экзогенным аллергическим альвеолитом. In the work has been studied prooxidant and antioxidant systems in the thymus of guinea pigs with experimental allergic alveolitis on 74-th, 84-th and 94-th day of the experiment. After the experiments it was found a gradual decrease in the activity of antioxidant enzymes and increasing the level of diene conjugates and malonic dialdehide, which can be important in the mechanism of formation of allergic alveolitis.